2004
DOI: 10.1128/jb.186.11.3286-3295.2004
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy of Cell Growth and Division in Staphylococcus aureus

Abstract: The growth and division of Staphylococcus aureus was monitored by atomic force microscopy (AFM) and thin-section transmission electron microscopy (TEM). A good correlation of the structural events of division was found using the two microscopies, and AFM was able to provide new additional information. AFM was performed under water, ensuring that all structures were in the hydrated condition. Sequential images on the same structure revealed progressive changes to surfaces, suggesting the cells were growing whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
184
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(217 citation statements)
references
References 46 publications
31
184
0
1
Order By: Relevance
“…As it is known from previous work that nascent cell wall adopts the ring structure 3,26 , the knobbles must be formed by remodelling of rings. Th e knobble structure has not previously been observed in whole cells by AFM or electron microscopy in which ' network ' or ' honeycomb ' structures, possibly combinations of peptidoglycan, protein and teichoic acids, have been reported, in addition to concentric rings 3,21,23,26 . Th e presence of rarely observed hybrid ring-knobble architectures suggests that remodelling occurs by lateral expansion of peptidoglycan, by discontinuous autolysis along the rings.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As it is known from previous work that nascent cell wall adopts the ring structure 3,26 , the knobbles must be formed by remodelling of rings. Th e knobble structure has not previously been observed in whole cells by AFM or electron microscopy in which ' network ' or ' honeycomb ' structures, possibly combinations of peptidoglycan, protein and teichoic acids, have been reported, in addition to concentric rings 3,21,23,26 . Th e presence of rarely observed hybrid ring-knobble architectures suggests that remodelling occurs by lateral expansion of peptidoglycan, by discontinuous autolysis along the rings.…”
Section: Discussionmentioning
confidence: 93%
“…Th e ring-banded surface is attributed to septal peptidoglycan and may be indicative of the alignment of glycan strands in the bulk material or of scarring resulting from the action of autolysins that split daughter cells 3 . Th ese surface structures have been seen in atomic force microscopy (AFM) images of living S. aureus 21 , as has an additional ' network ' or ' honeycomb ' surface arrangement 21 -23 . Sections viewed by transmission electron microscopy show that spherical cells are completely bisected by the septal disc before splitting 3,21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern recognition of this type is apparently regulated by the dimension of the MBL oligomers, suggesting the interesting possibility that the polydisperse nature of the MBL 3 oligomers, together with the surface exposure of ligands, has functional ramifications, although their biological significance remains to be studied. In this context, it is of considerable interest that recent studies of the bacterial cell wall of Gram-positive bacteria with AFM revealed repeating structural features (65,66), or patterns, with a periodicity of 10-20 nm (65). In the case of Gram-negative Pseudomonas aeruginosa, the pili were similarly demonstrated by AFM to contain structural features at the nanometer scale (67).…”
mentioning
confidence: 99%
“…However, the discovery of very short glycan strands has led to the proposal of a ''scaffold'' model in which the strands are oriented vertically in respect to the membrane (10,11), although this hypothesis is controversial (12). The application of high-resolution, atomic force microscopy (AFM) to the study of the structure of the outer surface of S. aureus and Bacillus atrophaeus cell wall peptidoglycan reveals a surface network of thin fibers (possibly of only a few glycan strands) with large empty spaces in between (13,14). This is supported by an NMR structural analysis in which a ''honeycomb'' architecture, based on the scaffold model, is proposed for the peptidoglycan of E. coli (15).…”
mentioning
confidence: 99%